A closer look at fertilizer legislations for silage maize across selected European countries: part II–overestimation of economically optimal nitrogen rates - Josephine Bukowiecki; Larissa Ullrich; Martin Komainda; Antje Herrmann; Kurt Möller; Frank Liebisch; Johannes Isselstein; Manfred Kayser; Michael Grunert; Henning Kage; Insa Kühling (Nutrient Cycling in Agroecosystems, 2026)
Silage maize cultivation in Central Europe offers significant potential for improving nitrogen (N) efficiency, but quantifying N savings under current fertilization regulations and identifying further opportunities for improvement remain crucial. This study addresses these gaps by analyzing the influence of site-specific and management factors on the economically optimal N fertilization rate (EONR). EONR was calculated for 223 yield response functions across diverse silage maize cultivation conditions using a quadratic-plateau function, which outperformed quadratic and linear-plateau models in describing maize yield response to increasing N rates. A linear regression model was developed through a multistage analysis, incorporating only significant parameters available at the start of the growing season to estimate EONR. These EONRs, along with representative silage maize cultivation scenarios, were used to evaluate N fertilization recommendations within national frameworks. Key influences included management practices affecting plant residue quantity and carbon-to-nitrogen ratios, along with weather and soil parameters. Optimal management for silage maize following grain cereals, the predominant pre-crop in many regions, involved straw removal and frost-killed non-legume winter cover crops to maximize N saving potential. Official N fertilization recommendations exceeded calculated EONRs on average by more than 14%, with minimal correlation (R 2 < 0.1). In contrast, the developed regression model estimated EONR with a R adj 2 of 0.30, highlighting key research areas and opportunities for improving N efficiency in silage maize cultivation in Central Europe.

A closer look at fertilizer legislations for silage maize across selected European countries: part I—insufficient consideration of net nitrogen mineralization - Josephine Bukowiecki; Larissa Ullrich; Martin Komainda; Antje Herrmann; Kurt Möller; Frank Liebisch; Kiril Manevski; Emanuel Jaufmann; Michael Grunert; Henning Kage; Insa Kühling (Nutrient Cycling in Agroecosystems, 2026)
Optimizing nitrogen (N) efficiency in European silage maize cultivation requires better quantification of N savings beyond existing regulations and identifying further opportunities to enhance efficiency. This study focuses on understanding how site and management factors influence net N mineralization. A comprehensive dataset from silage maize field trials across five Central European countries was analyzed using a multistage framework to develop a linear regression equation for estimating net N mineralization during the growing season based on key parameters known before the growing season. The final regression model, with a R adj 2 of 0.38, identified ten significant variables affecting net N mineralization. Evaluation of German and French fertilization frameworks, using representative regional use cases, indicated that national guidelines may underestimate or insufficiently capture net N mineralization. Major factors influencing soil net N mineralization included management practices impacting biomass quantity and the carbon-to-N ratio of plant residues, with N fertilization showing a negative effect on net N mineralization. Weather conditions and soil clay contributed to the observed variability to a lesser extent. For silage maize following grain cereals, a predominant cropping sequence within the investigated regions, the highest net N mineralization was achieved by combining straw removal with a frost-killed non-legume cover crop, suggesting potential for reduced N fertilization without yield loss.

Tunable electrochemical hydrogen evolution reaction employing surface acoustic waves - Michael J. Saule; Sixuan Wang; Rudolf Herrmann; Elmar Mitterreiter; Achim Wixforth; Ursula Wurstbauer; Christoph Westerhausen (Fuel, 2026)

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

A structured approach for the compliance analysis of battery systems with regard to the new EU Battery Regulation - Sönke Hansen; Tom Rüther; Mark Mennenga; Christoph Helbig; Gregor Ohnemüller; Filip Vysoudil; Constantin Wolf; Bernd Rosemann; Sandra Pavón; Alexander Michaelis; Thomas Vietor; Frank Döpper; et al. (Resources, Conservation and Recycling, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Examining site intervention efficacy and uncertainties with conceptual Bayesian networks: preventing offsite migration of DNAPL and contaminated groundwater - John F. Carriger; Michael C. Brooks; Carolyn Acheson; Ronald Herrmann; Lee Rhea (Environmental Science and Pollution Research, 2024)

Real-world characteristics and use patterns of patients treated with vericiguat: A nationwide longitudinal cohort study in Germany - Fabian Kerwagen; Christoph Ohlmeier; Thomas Evers; Stefan Herrmann; Inga Bayh; Alexander Michel; Silvia Kruppert; Joanna Wilfer; Rolf Wachter; Michael Böhm; Stefan Störk (European Journal of Clinical Pharmacology, 2024)
Purpose Vericiguat reduced clinical endpoints in patients experiencing worsening heart failure in clinical trials, but its implementation outside trials is unclear. Methods This retrospective analysis of longitudinally collected data was based on the IQVIA™ LRx database, which includes ~ 80% of the prescriptions of the 73 million people covered by the German statutory health insurance. Results Between September 2021 and December 2022, vericiguat was initiated in 2916 adult patients. Their mean age was 73 ± 13 years and 28% were women. While approximately 70% were uptitrated beyond 2.5 mg, only 36% reached 10 mg. Median time to up-titration from 2.5 mg to 5 mg was 17 (quartiles: 11–33) days, and from 2.5 to 10 mg 37 (25–64) days, respectively. In 87% of the patients, adherence to vericiguat was high as indicated by a medication possession ratio of ≥ 80%, and 67% of the patients persistently used vericiguat during the first year. Women and older patients reached the maximal dose of 10 mg vericiguat less often and received other substance classes of guideline-recommended therapy (GDMT) less frequently. The proportion of patients receiving four pillars of GDMT increased from 29% before vericiguat initiation to 44% afterwards. Conclusion In a real-world setting, despite higher age than in clinical trials, adherence and persistence of vericiguat appeared satisfactory across age categories. Initiation of vericiguat was associated with intensification of concomitant GDMT. Nevertheless, barriers to vericiguat up-titration and implementation of other GDMT, applying in particular to women and elderly patients, need to be investigated further.

Operationalization of life cycle engineering - Sami Kara; Christoph Herrmann; Michael Hauschild (Resources, Conservation and Recycling, 2023)

Citizen science’s transformative impact on science, citizen empowerment and socio-political processes - Julia von Gönner; Thora M. Herrmann; Till Bruckermann; Michael Eichinger; Susanne Hecker; Friederike Klan; Julia Lorke; Anett Richter; Ulrike Sturm; Silke Voigt-Heucke; Wiebke Brink; Christin Liedtke; et al. (Socio-Ecological Practice Research, 2023)
Citizen science (CS) can foster transformative impact for science, citizen empowerment and socio-political processes. To unleash this impact, a clearer understanding of its current status and challenges for its development is needed. Using quantitative indicators developed in a collaborative stakeholder process, our study provides a comprehensive overview of the current status of CS in Germany, Austria and Switzerland. Our online survey with 340 responses focused on CS impact through (1) scientific practices, (2) participant learning and empowerment, and (3) socio-political processes. With regard to scientific impact, we found that data quality control is an established component of CS practice, while publication of CS data and results has not yet been achieved by all project coordinators (55%). Key benefits for citizen scientists were the experience of collective impact (“making a difference together with others”) as well as gaining new knowledge. For the citizen scientists’ learning outcomes, different forms of social learning, such as systematic feedback or personal mentoring, were essential. While the majority of respondents attributed an important value to CS for decision-making, only few were confident that CS data were indeed utilized as evidence by decision-makers. Based on these results, we recommend (1) that project coordinators and researchers strengthen scientific impact by fostering data management and publications, (2) that project coordinators and citizen scientists enhance participant impact by promoting social learning opportunities and (3) that project initiators and CS networks foster socio-political impact through early engagement with decision-makers and alignment with ongoing policy processes. In this way, CS can evolve its transformative impact.

Static and dynamic methods in social network analysis reveal the association patterns of desert-dwelling giraffe - Emma E. Hart; Simone Ciuti; Leticia Herrmann; Julian Fennessy; Emma Wells; Michael Salter-Townshend (Behavioral Ecology and Sociobiology, 2022)

Nematode biphasic ‘boom and bust’ dynamics are dependent on host bacterial load while linking dauer and mouth‐form polyphenisms - Tess Renahan; Wen‐Sui Lo; Michael S. Werner; Jacques Rochat; Matthias Herrmann; Ralf J. Sommer (Environmental Microbiology, 2021)
Cross‐kingdom interactions involve dynamic processes that shape terrestrial ecosystems and represent striking examples of co‐evolution. The multifaceted relationships of entomopathogenic nematodes with their insect hosts and symbiotic bacteria are well‐studied cases of co‐evolution and pathogenicity. In contrast, microbial interactions in soil after the natural death of insects and other invertebrates are minimally understood. In particular, the turnover and succession of nematodes and bacteria during insect decay have not been well documented ‐ although it represents a rich ecological niche with multiple species interactions. Here, we utilize developmentally plastic nematode Pristionchus pacificus and its associated scarab beetles as models. On La Réunion Island, we collected rhinoceros beetle Oryctes borbonicus , induced death, and placed carcasses in cages both on the island and in a mock‐natural environment in the laboratory controlling for high spatial and temporal resolution. Investigating nematode population density and dispersal dynamics, we were able to connect two imperative plasticities, dauer and mouth form. We observed a biphasic ‘boom and bust’ dispersal dynamic of dauer larvae that corresponds to bacterial load on carcasses but not bacterial type. Strikingly, all post‐dauer adults have the predatory mouth form, demonstrating novel intricate interactions on decaying insect hosts. Thus, ecologically relevant survival strategies incorporate critical plastic traits.

Mit der Modellkette RCP-GCM-RCM-mGROWA projizierte Grundwasserneubildung als Datenbasis für zukünftiges Grundwassermanagement in Nordrhein-Westfalen - Frank Herrmann; Klaus Keuler; Tim Wolters; Sabine Bergmann; Michael Eisele; Frank Wendland (Grundwasser, 2021)
Zusammenfassung Mit einem Multi-Modell-Ensemble wurde analysiert, wie sich der Klimawandel auf den Grundwasserhaushalt in Nordrhein-Westfalen (NRW) auswirkt. Hierzu wurden Projektionen der zukünftigen Grundwasserneubildung für insgesamt 36 Mitglieder der Modellkette RCP-GCM-RCM-mGROWA, bestehend aus 3 RCP-Szenarien zukünftiger globaler Erwärmung, 6 globalen und 5 dynamischen regionalen Klimamodellen sowie dem Wasserhaushaltsmodell mGROWA, vorgenommen. Mit dem Ensemble wurden für die hydrogeologischen Großräume NRWs nur teilweise signifikante Änderungen der jährlichen Grundwasserneubildung in den Perioden 2011–2040, 2041–2070 und 2071–2100 projiziert. Ein Robustheitstest mit zwei Kriterien (Übereinstimmung und Signifikanz der Änderungssignale) liefert keine belastbare Begründung dafür, dass sich die Grundwasserneubildung bis 2100 systematisch und signifikant ändern wird. Aus statistischer Perspektive wird deshalb die Schlussfolgerung gezogen, dass in NRW langfristig eine Grundwasserneubildung erwartet werden kann, die sich nicht grundlegend vom Niveau der Periode 1971–2000 unterscheidet. Hydro-meteorologisch befindet sich NRW in einer Übergangszone, in der eine Zunahme der Winterniederschläge die Wirkung der Erwärmung auf die Grundwasserneubildung wahrscheinlich kompensiert.

Multiphase-field modelling of crack propagation in geological materials and porous media with Drucker-Prager plasticity - Michael Späth; Christoph Herrmann; Nishant Prajapati; Daniel Schneider; Felix Schwab; Michael Selzer; Britta Nestler (Computational Geosciences, 2021)
A multiphase-field approach for elasto-plastic and anisotropic brittle crack propagation in geological systems consisting of different regions of brittle and ductile materials is presented and employed to computationally study crack propagation. Plastic deformation in elasto-plastic materials such as frictional, granular or porous materials is modelled with the pressure-sensitive Drucker-Prager plasticity model. This plasticity model is combined with a multiphase-field model fulfilling the mechanical jump conditions in diffuse solid-solid interfaces. The validity of the plasticity model with phase-inherent stress and strain fields is shown, in comparison with sharp interface finite element solutions. The proposed model is capable of simulating crack formation in heterogeneous multiphase systems comprising both purely elastic and inelastic phases. We investigate the influence of different material parameters on the crack propagation with tensile tests in single- and two-phase materials. To show the applicability of the model, crack propagation in a multiphase domain with brittle and elasto-plastic components is performed.

COR-101, ein menschlicher Antikörper gegen COVID-19 - Stefan Dübel; Andreas Herrmann; Thomas Schirrmann; André Frenzel; Michael Hust (BIOspektrum, 2021)
COR-101 is a fully human, Fc silenced IgG that was discovered by antibody phage display. It reduced the SARS-CoV-2 virus load in the lung by more than 99 percent in Hamster models and led to much faster recovery. Its mode of action has been elucidated by solving the atomic structure of its interaction with SARS-CoV-2. The antibody competes with ACE2 binding by blocking a large area of the SARS-CoV-2 spike protein.

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

Bax inhibitor-1 deficiency leads to obesity by increasing Ca2+-dependent insulin secretion - Koenraad Philippaert; Michael Roden; Dmitrij Lisak; Diones Bueno; Tomas Jelenik; Konstantin Radyushkin; Teresa Schacht; Margot Mesuere; Verena Wüllner; Ann-Kathrin Herrmann; Jan Baumgart; Rudi Vennekens; et al. (Journal of Molecular Medicine, 2020)
Transmembrane BAX inhibitor motif containing 6 (TMBIM6), also known as Bax inhibitor-1, is an evolutionarily conserved protein involved in endoplasmic reticulum (ER) function. TMBIM6 is an ER Ca 2+ leak channel and its deficiency enhances susceptibility to ER stress due to inhibition of the ER stress sensor IRE1α. It was previously shown that TMBIM6 overexpression improves glucose metabolism and that TMBIM6 knockout mice develop obesity. We here examined the metabolic alterations underlying the obese phenotype and subjected TMBIM6 knockout mice to indirect calorimetry and euglycemic-hyperinsulinemic tests with stable isotope dilution to gauge tissue-specific insulin sensitivity. This demonstrated no changes in heat production, food intake, activity or hepatic and peripheral insulin sensitivity. TMBIM6 knockout mice, however, featured a higher glucose-stimulated insulin secretion in vivo as assessed by the hyperglycemic clamp test and hepatic steatosis. This coincided with profound changes in glucose-mediated Ca 2+ regulation in isolated pancreatic β cells and increased levels of IRE1α levels but no differences in downstream effects of IRE1α like increased Xbp1 mRNA splicing or Ire1-dependent decay of insulin mRNA in the pancreas. We therefore conclude that lack of TMBIM6 does not affect insulin sensitivity but leads to hyperinsulinemia, which serves to explain the weight gain. TMBIM6-mediated metabolic alterations are mainly caused by its role as a Ca 2+ release channel in the ER. Key messages TMBIM6 −/− leads to obesity and hepatic steatosis. Food intake and energy expenditure are not changed in TMBIM6 −/− mice. No changes in insulin resistance in TMBIM6 −/− mice. Increased insulin secretion caused by altered calcium dynamics in β cells.

Brittle anisotropic fracture propagation in quartz sandstone: insights from phase-field simulations - Nishant Prajapati; Christoph Herrmann; Michael Späth; Daniel Schneider; Michael Selzer; Britta Nestler (Computational Geosciences, 2020)
We developed a generalized multiphase-field modeling framework for addressing the problem of brittle fracture propagation in quartz sandstones at microscopic length scale. Within this numerical approach, the grain boundaries and crack surfaces are modeled as diffuse interfaces. The two novel aspects of the model are the formulations of (I) anisotropic crack resistance in order to account for preferential cleavage planes within each randomly oriented quartz grain and (II) reduced interfacial crack resistance for incorporating lower fracture toughness along the grain boundaries that might result in intergranular crack propagation. The presented model is capable of simulating the competition between inter- and transgranular modes of fracturing based on the nature of grain boundaries, while exhibiting preferred fracturing directions within each grain. In the full parameter space, the model can serve as a powerful tool to investigate the complicated fracturing processes in heterogeneous polycrystalline rocks comprising of grains of distinct elastic properties, cleavage planes, and grain boundary attributes. We demonstrate the performance of the model through the representative numerical examples.

Seasonal and Interannual Variability in Net Ecosystem Production of a Subtropical Coastal Lagoon Inferred from Monthly Oxygen Surveys - Lauren E. Seidensticker; Raymond G. Najjar; Maria Herrmann; Joseph N. Boyer; Henry O. Briceño; W. Michael Kemp; Daniel J. Tomaso (Estuaries and Coasts, 2019)

The spatial distribution of soil organic carbon in tidal wetland soils of the continental United States - Audra L. Hinson; Rusty A. Feagin; Marian Eriksson; Raymond G. Najjar; Maria Herrmann; Thomas S. Bianchi; Michael Kemp; Jack A. Hutchings; Steve Crooks; Thomas Boutton (Global Change Biology, 2017)
Tidal wetlands contain large reservoirs of carbon in their soils and can sequester carbon dioxide ( CO 2 ) at a greater rate per unit area than nearly any other ecosystem. The spatial distribution of this carbon influences climate and wetland policy. To assist with international accords such as the Paris Climate Agreement, national‐level assessments such as the United States (U.S.) National Greenhouse Gas Inventory, and regional, state, local, and project‐level evaluation of CO 2 sequestration credits, we developed a geodatabase (CoBluCarb) and high‐resolution maps of soil organic carbon ( SOC ) distribution by linking National Wetlands Inventory data with the U.S. Soil Survey Geographic Database. For over 600,000 wetlands, the total carbon stock and organic carbon density was calculated at 5‐cm vertical resolution from 0 to 300 cm of depth. Across the continental United States, there are 1,153–1,359 Tg of SOC in the upper 0–100 cm of soils across a total of 24 945.9 km 2 of tidal wetland area, twice as much carbon as the most recent national estimate. Approximately 75% of this carbon was found in estuarine emergent wetlands with freshwater tidal wetlands holding about 19%. The greatest pool of SOC was found within the Atchafalaya/Vermilion Bay complex in Louisiana, containing about 10% of the U.S. total. The average density across all tidal wetlands was 0.071 g cm −3 across 0–15 cm, 0.055 g cm −3 across 0–100 cm, and 0.040 g cm −3 at the 100 cm depth. There is inherent variability between and within individual wetlands; however, we conclude that it is possible to use standardized values at a range of 0–100 cm of the soil profile, to provide first‐order quantification and to evaluate future changes in carbon stocks in response to environmental perturbations. This Tier 2‐oriented carbon stock assessment provides a scientific method that can be copied by other nations in support of international requirements.

Peripheral Alterations in Cytokine and Chemokine Levels After Antidepressant Drug Treatment for Major Depressive Disorder: Systematic Review and Meta-Analysis - Cristiano A. Köhler; Thiago H. Freitas; Brendon Stubbs; Michael Maes; Marco Solmi; Nicola Veronese; Nayanna Q. de Andrade; Gerwyn Morris; Brisa S. Fernandes; André R. Brunoni; Nathan Herrmann; Charles L. Raison; et al. (Molecular Neurobiology, 2017)

The Ocean's Vital Skin: Toward an Integrated Understanding of the Sea Surface Microlayer - Anja Engel; Hermann W. Bange; Michael Cunliffe; Susannah M. Burrows; Gernot Friedrichs; Luisa Galgani; Hartmut Herrmann; Norbert Hertkorn; Martin Johnson; Peter S. Liss; Patricia K. Quinn; Markus Schartau; et al. (Frontiers in Marine Science, 2017)

Compilation of processing factors and evaluation of quality controlled data of food processing studies - Rebekka Scholz; Michael Herrmann; Britta Michalski (Journal of Consumer Protection and Food Safety, 2017)

Ist NGS der bessere Spürhund bei Akuter Lymphatischer Leukämie? - Henrik Knecht; Marc Füllgrabe; Heiko Trautmann; Dietrich Herrmann; Matthias Ritgen; Michael Kneba; Christiane Pott; Monika Brüggemann (BIOspektrum, 2015)

Life Cycle Engineering and Sustainable Manufacturing - Christoph Herrmann; Michael Hauschild; Timothy Gutowski; Reid Lifset (Journal of Industrial Ecology, 2014)

Confronting Uncertainty in Life Cycle Assessment Used for Decision Support - Ivan T. Herrmann; Michael Z. Hauschild; Michael D. Sohn; Thomas E. McKone (Journal of Industrial Ecology, 2014)
Summary The aim of this article is to help confront uncertainty in life cycle assessments (LCAs) used for decision support. LCAs offer a quantitative approach to assess environmental effects of products, technologies, and services and are conducted by an LCA practitioner or analyst (AN) to support the decision maker (DM) in making the best possible choice for the environment. At present, some DMs do not trust the LCA to be a reliable decision‐support tool—often because DMs consider the uncertainty of an LCA to be too large. The standard evaluation of uncertainty in LCAs is an ex‐post approach that can be described as a variance simulation based on individual data points used in an LCA. This article develops and proposes a taxonomy for LCAs based on extensive research in the LCA, management, and economic literature. This taxonomy can be used ex ante to support planning and communication between an AN and DM regarding which type of LCA study to employ for the decision context at hand. This taxonomy enables the derivation of an LCA classification matrix to clearly identify and communicate the type of a given LCA. By relating the LCA classification matrix to statistical principles, we can also rank the different types of LCA on an expected inherent uncertainty scale that can be used to confront and address potential uncertainty. However, this article does not attempt to offer a quantitative approach for assessing uncertainty in LCAs used for decision support.

Enabling optimization in LCA: from “ad hoc” to “structural” LCA approach—based on a biodiesel well-to-wheel case study - Ivan T. Herrmann; Martin Lundberg-Jensen; Andreas Jørgensen; Thomas Stidsen; Henrik Spliid; Michael Hauschild (The International Journal of Life Cycle Assessment, 2014)

Sun Protection Training Based on a Theater Play for Preschoolers: an Effective Method for Imparting Knowledge on Sun Protection? - Nadja Seidel; Friederike Stoelzel; Marlene Garzarolli; Sandra Herrmann; Eckhard Wilhelm Breitbart; Hendrik Berth; Michael Baumann; Gerhard Ehninger (Journal of Cancer Education, 2013)

Potential for optimized production and use of rapeseed biodiesel. Based on a comprehensive real-time LCA case study in Denmark with multiple pathways - Ivan T. Herrmann; Andreas Jørgensen; Sander Bruun; Michael Z. Hauschild (The International Journal of Life Cycle Assessment, 2013)

HIV neuropathy: an in vivo confocal microscopic study - Jorge L. Almodovar; Giovanni Schifitto; Michael P. McDermott; Michele Ferguson; David N. Herrmann (Journal of NeuroVirology, 2012)

H-D exchange on graphite–potassium intercalation compounds - Siegbert Rummel; Michael Herrmann; Manfred Wahren; Safar M. Yunusov; Margarita A. Ilatovskaya; Yuri B. Isaev; N. D. Lapkina; Yuri N. Novikov; Vladimir B. Shur (Isotopes in Environmental and Health Studies, 2012)

Variants of guided self-organization for robot control - Georg Martius; J. Michael Herrmann (Theory in Biosciences, 2012)

Technology-specific error signatures in the 1000 Genomes Project data - Michael Nothnagel; Alexander Herrmann; Andreas Wolf; Stefan Schreiber; Matthias Platzer; Reiner Siebert; Michael Krawczak; Jochen Hampe (Human Genetics, 2011)

Resurrecting an extinct species: archival DNA, taxonomy, and conservation of the Vegas Valley leopard frog - Evon R. Hekkala; Raymond A. Saumure; Jef R. Jaeger; Hans-Werner Herrmann; Michael J. Sredl; David F. Bradford; Danielle Drabeck; Michael J. Blum (Conservation Genetics, 2011)

Compositionality of arm movements can be realized by propagating synchrony - Alexander Hanuschkin; J. Michael Herrmann; Abigail Morrison; Markus Diesmann (Journal of Computational Neuroscience, 2011)

The Cardiac Effects of Prolonged Vitamin B12 and Folate Deficiency in Rats - Omid Taban-Shomal; Heiko Kilter; Alexandra Wagner; Heike Schorr; Natalia Umanskaya; Ulrich Hübner; Michael Böhm; Wolfgang Herrmann; Markus Herrmann (Cardiovascular Toxicology, 2009)

A neurocomputational model for optimal temporal processing - Joachim Haß; Stefan Blaschke; Thomas Rammsayer; J. Michael Herrmann (Journal of Computational Neuroscience, 2008)

Symmetries, non-Euclidean metrics, and patterns in a Swift–Hohenberg model of the visual cortex - N. Michael Mayer; Matthew Browne; J. Michael Herrmann; Minoru Asada (Biological Cybernetics, 2008)

Bioassay-directed Fractionation of Organic Extracts of Marine Surface Sediments from the North and Baltic Sea - Part II: Results of the biotest battery and development of a biotest index (8 pp) - Ulrike Kammann; Scarlett Biselli; Ninja Reineke; Werner Wosniok; Dirk Danischewski; Heinrich Hühnerfuss; Angelika Kinder; Arne Sierts-Herrmann; Norbert Theobald; Hans-Heinrich Vahl; Michael Vobach; Johannes Westendorf; et al. (Journal of Soils and Sediments, 2005)

Shaping of Receptive Fields in the Visual Cortex During Retinal Maturation - Norbert Mayer; J. Michael Herrmann; Theo Geisel (Journal of Computational Neuroscience, 2003)

Dynamical systems for predictive control of autonomous robots - J. Michael Herrmann (Theory in Biosciences, 2001)

Association analysis of GABA A β2 and γ2 gene polymorphisms with event-related prefrontal activity in man - Georg Winterer; Michael Smolka; Jerzy Samochowiec; Christoph Mulert; Mario Ziller; Richard Mahlberg; Yvonne Wuebben; Jürgen Gallinat; Hans Rommelspacher; Werner Herrmann; Thomas Sander (Human Genetics, 2000)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)